CTNI-03. EXTENDED BENEFITS IN PATIENTS WITH RECURRENT HIGH GRADE GLIOMA THAT CONTINUOUSLY RECEIVE TOCA FC AFTER TOCA 511 TREATMEN. (12th November 2021) - Walbert, Tobias; Damek, Denise; Nina, L Martinez; Piccioni, David; Singer, Samuel; Cloughesy, Timothy
Abstract: Toca 511 (vocimagene amiretrorepvec) is an investigational nonlytic, retroviral replicating vector (RRV) constructed with a codon-optimized yeast cytosine deaminase (CD) gene. Toca 511 infects cancer cells, and stably delivers CD gene whose protein product converts courses of the prodrug TocaFC (5-fluorocytosine) into 5-fluorouracil (5-FU). Several phase 1 studies and a phase 2/ 3 clinical study tested Toca511 in combination with TocaFC in patients undergoing planned resection for recurrent glioblastoma (rGBM) or anaplastic astrocytoma (rAA). The last trial was completed in 2019, and although the Phase 2/3 study did not meet the primary objective, patients who appeared to benefit from the treatment elected to continue TocaFC through an expanded access or compassionate use pathway. Seven patients continued on treatment: 3 men and 4 women; 5 with rGBM, 2 with rAA. Duration of treatment with TocaFC ranges from 29 months to 7 years and 5 months (average 49.2 months). Six patients who are still on active treatment with TocaFC have either stable disease or complete response. TocaFC is well tolerated in these patients, typical side effects include diarrhea. Some patients with rGBM or rAA appear to benefit from extended TocaFC treatment after Toca511. Individual cases will be discussed.